2019
DOI: 10.1200/jgo.19.00043
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Unmet Supportive Needs of Nigerian Patients With Cancer

Abstract: PURPOSE Diagnosis and treatment of cancer are associated with significant psychological distress, and patients face a broad range of challenges that create a vacuum of unmet needs felt by patients, such as a loss of personal control and frustration. The aim of the current study was to determine the magnitude, distribution, and correlates of unmet needs in Nigerian patients with cancer. PATIENTS AND METHODS Using a descriptive cross-sectional approach, we assessed 205 patients with cancer who attended oncology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Among a sample of Korean patients with cancer, the prevalence of high DT score was 28.8% [41], while the prevalence of high GHQ score from another study was 35.1%, with varying rate from 43.4% for lung cancer to 29.6% for gynecological cancers [42]. The high prevalence of psychological and psychosocial distress in our sample could be adduced to several factors, including the lack of adequate cancer support system and crises intervention network that handle psychosocial problems among cancer patients leading to a high unmet needs [43]. The emotional responses may also be due to physical symptoms such as pain, nausea, lymphoedema, and other distressing symptoms of the disease and unwanted side effects of cancer treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Among a sample of Korean patients with cancer, the prevalence of high DT score was 28.8% [41], while the prevalence of high GHQ score from another study was 35.1%, with varying rate from 43.4% for lung cancer to 29.6% for gynecological cancers [42]. The high prevalence of psychological and psychosocial distress in our sample could be adduced to several factors, including the lack of adequate cancer support system and crises intervention network that handle psychosocial problems among cancer patients leading to a high unmet needs [43]. The emotional responses may also be due to physical symptoms such as pain, nausea, lymphoedema, and other distressing symptoms of the disease and unwanted side effects of cancer treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Such unmet BCS needs include the inadequate provision of specific BC information needs, inadequate provision and use of BC prevention services, patients’ experiences and satisfaction with service provision, and inefficiencies in service delivery. 52 , 53 Addressing these needs through appropriate health interventions by healthcare professionals (doctors, nurses, and community health workers), stakeholders in the health sector, Federal and State Ministries of Health could allay BCS fear and boost self-efficacy for BCS uptake among middle-aged Nigerian women.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study done in the United Kingdom stated that onequarter of the patients reported unmet supportive care needs [14]. According to a survey done in Africa, nearly 46% of the participants indicated supportive care unmet needs [15]. Unmet needs have been categorised into these major domains: physical, psychological, informational, patient care and sexual needs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Different researchers have found that the largest unmet needs are related to the psychological needs domain [17][18][19], and in much lesser frequency is found in patient care and sexual domains [20,21]. A systematic review in Asia and Africa showed that psychological, physical and healthcare service/information domains were the three most commonly reported domains of unmet needs for cancer patients [15,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation